KONSEP IBU SEBAGAI PENDIDIK PERTAMA DALAM KELUARGA ANALISIS TERHADAP BUKU UMMUL MUKMININ KARYA SYEKH ABDUL HAMID MAHMUD THAHMAZ - Yulistri Yulistri; Ismail Sukardi; Abu Mansur (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2021)
The study aims to: (1) to learn mother's concept as the first educator of the family analysis in sheikh abdul hamid mahmud thahmaz's book ummul mukminin. (2) to learn the unique thinking of abdul hamid mahmud thahmaz about mother as the first educator in his book ummul mukminin that sets it apart from other ideas. The type of research used in this study is a type of research study with a descriptive qualitative approach. The literature study of data-collecting techniques is a study referring to libraries that refer to books, journals, reports, documents or other scientific works. The data analysis techniques used are data reduction, display and data verification. Content analysis is an analysis by discussing reference material relating to the mother's concept as the first educator in the family (analysis of the book ummul mukminin). This study has shown that the important role parents play in educating their children. As a mother's role as an educator in the family should have a certain number of characteristics as a prerequisite. In his book ummul mukminin sheikh abdul hamid mahmud thahmaz set the aisyah r.a. character as an example for mothers who wanted to be good children educators in the family. Such characteristics are: zuhud, the aisyah, philanthropy, the character, and the learning. And the thinking of sheikh abdul hamid mahmud thahmaz of mother as a educator must be historical, normistic, and philosophical